Senior Universities and Active Aging: the impacts on the elderly in Portugal - Páscoa, Gina Maria Gouveia (2019)
This article discusses the theme of senior universities and active aging and their importance in the lives of the elderly. This is a critical literature review that addresses the issue of aging in the social context from the current offer of participation of older people in senior universities. In this context, the foundation of these institutions, at an international and national level, is analyzed, highlighting a senior university located in the interior of Portugal, more concretely in the city of Castelo Branco, known as Senior University Albicastrense (USALBI).